Targeting uPAR by CRISPR/Cas9 System Attenuates Cancer Malignancy and Multidrug Resistance - Wang, Kun; Xing, Zi-Hao; Jiang, Qi-Wei; Yang, Yang; Huang, Jia-Rong; Yuan, Meng-Ling; Wei, Meng-Ning; Li, Yao; Wang, Sheng-Te; Liu, Kun; Shi, Zhi (Frontiers in Oncology, 2019)
Urokinase plasminogen activator receptor (uPAR), a member of the lymphocyte antigen 6 protein superfamily, is overexpressed in different types of cancers and plays an important role in tumorigenesis and development. In this study, we successfully targeted uPAR by CRISPR/Cas9 system in two human cancer cell lines with two individual sgRNAs. Knockout of uPAR inhibited cell proliferation, migration and invasion. Furthermore, knockout of uPAR decreases resistance to 5-FU, cisplatin, docetaxel and doxorubicin in these cells. Although there are several limitations in the application of CRISPR/Cas9 system for cancer patients, our study offers valuable evidences for the role of uPAR in cancer malignancy and drug resistance.